Magnetic Materials: Robust Manipulation of Magnetism in Dilute Magnetic Semiconductor (Ga, Mn)As by Organic Molecules (Adv. Mater. 48/2015). (December 2015) - Wang, Xiaolei; Wang, Hailong; Pan, Dong; Keiper, Timothy; Li, Lixia; Yu, Xuezhe; Lu, Jun; Lochner, Eric; von Molnár, Stephan; Xiong, Peng; Zhao, Jianhua
Abstract : As described by P. Xiong, J. Zhao, and co‐workers on page 8043, surface adsorption of organic molecules can lead to robust manipulation of ferromagnetism in (Ga, Mn)As and a surface‐preparation protocol enables direct writing of nanopatterns of self‐assembled organic monolayers on the surface of the (Ga, Mn). As by dip‐pen nanolithography; arbitrary nanopatterns, such as the "GaMnAs" characters, can be created. These two breakthroughs point to a novel pathway of controlled nanoscale manipulation of magnetism in dilute magnetic semiconductors via surface molecular patterning, which may lead to a new paradigm for the flexible fabrication of erasable and reconfigurable magnetic nanostructures and devices.